Instability of the Economy and Fragility of the Financial Structure - Jan A. Kregel (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1993)
This paper seeks to extend Coase's explanation of the existence of firms in general to financial firms and the financial markets in particular. Fianancial firms are defined as "producting prices" of financial assets. It also seeks to describe market structure in terms of constellations of different types of financial firms, leading to a continuum of a market configurations ranging from less to more internal integration of financial market structures are compared and assessed. Finally, the symbiosis between manufacturing and financial structures is discussed.
Keywords: 330